-3(2w-6)+4(-1-5w)=0

Simple and best practice solution for -3(2w-6)+4(-1-5w)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2w-6)+4(-1-5w)=0 equation:


Simplifying
-3(2w + -6) + 4(-1 + -5w) = 0

Reorder the terms:
-3(-6 + 2w) + 4(-1 + -5w) = 0
(-6 * -3 + 2w * -3) + 4(-1 + -5w) = 0
(18 + -6w) + 4(-1 + -5w) = 0
18 + -6w + (-1 * 4 + -5w * 4) = 0
18 + -6w + (-4 + -20w) = 0

Reorder the terms:
18 + -4 + -6w + -20w = 0

Combine like terms: 18 + -4 = 14
14 + -6w + -20w = 0

Combine like terms: -6w + -20w = -26w
14 + -26w = 0

Solving
14 + -26w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -26w = 0 + -14

Combine like terms: 14 + -14 = 0
0 + -26w = 0 + -14
-26w = 0 + -14

Combine like terms: 0 + -14 = -14
-26w = -14

Divide each side by '-26'.
w = 0.5384615385

Simplifying
w = 0.5384615385

See similar equations:

| w*7*w*3*w=131 | | 40x^4-60x^3+20x=0 | | 5x-2=-3x+6 | | (3x+y)6= | | 5(y-2)-2=2(v+1)-5 | | 5B+3V=27.50 | | (x^2)-x-10=0 | | 4x^2+4=148 | | 5x-12-23x=6(-3x-2) | | 46-46x=(7x+3)(x-1) | | p=12x-5x | | 6-4x=4(1-x) | | 35-(2x-14)=40-(x+2) | | (2x^2)-x-(3)=0 | | 5x^2=23x+10 | | 40-7n=2(-5n+6)-n | | 8w/6+8=w-2 | | 12(4x-6)=8x+5(8x-6) | | 6s=-3T | | 5s=8t+12 | | 4(2x-1)-(-3x-5)=-179 | | 10b+5=76+5 | | 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 | | 5(x+8)-2x=60 | | 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 |

Equations solver categories